What is the Global View of Women's Leadership? Sentiment Analysis based on Meta-Analysis - Laela, Ela; Taufiq, Adhitya Rahmat; Mandasari, Andina Eka (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
This research aims to analyze literature about leadership women and integrate diverse perspectives with meta-analysis and sentiment analysis. This research uses a design study combined qualitative with analysis statistics descriptive for meta-analysis and analysis sentiment. The search sample uses a purposive sampling technique. This study analyzes articles on Dimension.ai metadata about women's leadership from 2015 to 2022. Keywords used for data collection, namely